The Effect of Reforms and Satisfaction on Corruption Perception - Mehawesh, Sada S.; Al-Badayneh, Diab M. (Journal of Posthumanism, 2025)
This study examines the impact of reform and satisfaction with government efforts on overall perceptions of corruption on Qatari citizens’ perceptions of corruption. Using a structured questionnaire, this study measured three main scales: corruption perceptions (42 items), satisfaction with government effort (10 items), and demographic information from a sample of 238 (116 men and 117 women, mean age = 32). The face validity (97%) and construct validity of the questionnaire were found to be high with a significant correlation (r = .276, p = .000). Evidence for reliability was provided with Cronbach’s alpha coefficients of .90 for all scales. The optimization results show that the satisfaction level for the whole government performance and public sector is higher than other evaluated features, meaning that people are more satisfied with these items. In contrast, satisfaction with the private sector and the administrative control and transparency authority was significantly lower. The multiple correlation coefficient (R = .30) reflects a medium relationship when both reforms and satisfaction explain 9% of the variance in perception with corruption, emphasizing their effect at the will of public opinion. Results Regression analysis showed that the effect of reform and satisfaction on corruption perception was significant (F = 4.478, α = .014), highlighting the significance of reform strategy and transparency efforts to improve trust perceptions and decrease corruption perception in Qatar. The results highlight the need to focus on satisfying public corruption perceptions in order to improve government anti-corruption programs in view of Qatar.